(untitled) (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
There is increasing interest in conserving plant endemics because they face a high risk of extinction in their natural habitats and support traditional functions for local communities. This perspective review paper aims to provide a view of the future of the ethnobotany of Xanthostemon novoguineensis, which can be used to conserve this plant in the forests of Papua Province, Indonesia. Thus, it is presented as a personal view on critical thinking about future challenges to protecting this plant. First, the history of this plant is described, from its invention in Papua New Guinea. Subsequently, a discussion of the ethnobotanical perspective on the conservation of X. novoguineensis, based on a recent literature review, is provided. The final section discusses the near-future challenge associated with X. novoguineensis and how the ethnobotanical perspective of Papuans, especially the Sentani tribes, may hold vital value for the sustainability of X. novoguineensis.